Identifying and Ranking the Important Textual and Paratextual Elements in Fiction Retrieval - Sakineh Gasempour; Zoya Abam; Roya Baradar (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2021)
Purpose: The purpose of this study is to identify the textual and paratextual elements in retrieving fiction from the readers’ perspective in order to provide the most appropriate access points for the readers and to improve access to fictions based on the readers’ needs. Method: The current research is an applied study in terms of purpose, applying a mixed method that was conducted using the sequential exploratory strategy. The statistical population in both stages of the study were readers of fiction literature who were selected by purposive sampling strategy. In the first stage of the study, 14 fiction readers participated in a semi-structured interview. The collected data were coded and analyzed based on the six-step content analysis framework of Brown and Clark using MAXQDA software (2018 version). In the second stage, the opinions of 12 experts in the field of fiction were used to weigh and determine the importance of each textual and paratextual element. The data collection tool at this stage was a pairwise comparison questionnaire designed based on a 9-point scale. Expert Choice software (version 11) was used to analyze the data in this stage. Findings: According to the results of the first stage of this study, 24 textual and paratextual elements in the form of 6 main themes were identified by a thematic analysis of the interviews. Then, according to experts, 19 of these extracted elements were selected as important elements in fiction retrieval. In general, the results confirmed that from the readers’ point of view, textual and paratextual elements could be useful in understanding, evaluating, determining and selecting sources, and help fiction readers to find relevant fictions. By use of textual and paratextual elements of fiction to enrich library catalogues and create several access points, we can improve fiction retrieval. Therefore, it is suggested that these elements be used in the design and development of retrieval systems in libraries in order to increase the efficiency of these systems and enable successful search and retrieval for fiction readers. Originality/value: The results of this study provide a starting point for the development and design of fiction search and retrieval systems based on the needs of the reader. By using both textual and paratextual elements of fiction to enrich library catalogs and create several access points, we can develop and improve search and retrieval systems and increase the efficiency of this systems in retrieving fictions which readers want.